Factors Influencing Financial Performance Through Sustainability Reporting in Indonesia - Luk Luk Fuadah; Rika Henda Safitri; Yuliani Yuliani (Faculty of Economics, Universitas Sriwijaya, 2019)
The study aims to examine factors influence financial performance through sustainability reporting. The sample is companies that received an Indonesia Sustainability Reporting Awards (ISRA) in 2016. This study uses secondary data from the annual report 2012-2016. The first result shows that board size and sustainability are not significant. The second and third result shows the size and leverage have a positive impact on sustainability reporting. The last result shows that sustainability reporting has a positive and significant effect on financial performance. The contributions in this study, first, it shows the mediating effect of sustainability reporting on the relationship between these factors and financial performance. Second, this study also investigates companies that received ISRA in 2016. The limitation of this study is that it focuses on companies that received the award fromISRA in 2016. Another limitation, the framework is not the best framework.